PENGARUH PENAMBAHAN SERAT KAIN KATUN PAKAIAN BEKAS TERHADAP KEKUATAN TEKAN DAN BENDING DARI KOMPOSIT FOAM AGENT BETON RINGAN DENGAN STRIMIN BAJA - Septiawan P, Muh. Rian; Catur, Agus Dwi; Pandiatmi, Pandri (Energy, Materials and Product Design, 2023)
The problem of waste is a problem that requires serious handling, especially inorganic waste, where this waste cannot be destroyed by nature in a short time. Indonesia itself does not have a special treatment for this used clothing waste. Used clothes that are still fit for use can be resold or donated to those in need, but not every second-hand clothes can be reused so that used clothes are only thrown away which can cause pollution to the surrounding environment. With the increase in the human population in the world, the needs also increase, such as the need for food, clothing and there is also an increasing need for buildings. Panels are one of the most widely used building materials, especially for insulating walls in house buildings. One type of panel is a lightweight concrete panel. The purpose of this study is to utilize used clothing waste as a part of lightweight concrete composites where the fibers of used clothing waste are utilized as reinforcement for lightweight concrete composites and to determine the effect of adding used clothing waste fibers to the compressive and bending strength of the lightweight concrete. The variations that will be used are 0%, 0.3% and 0.7% with the size of the mold for bending, which is 160 mm long, 40 mm wide, 40 mm thick. while for the compression test mold is cylindrical in shape and has a height of 300 mm and a diameter of 150 mm. The results of this study indicate that there is an increase in strength in the compressive test from not using fiber or 0% of 4.42 N/mm2 , using fiber with a variation of 0.3% of 5.47 N/mm2 and fiber with a variation of 0.7% of 6.13 N/mm2 . The bending test shows a decrease in strength from variations of 0%, 0.3%, 0.7% to 3.65 Mpa, 3.376 Mpa, 2.6 Mpa.